COMPARISON OF ENVIRONMENTAL LAW ENFORCEMENT WITH CIVIL LAW AND ADMINISTRATIVE LAW - Nita Nurvita; jelly leviza (LEX SOCIETAS: Journal of Law and Public Administration, 2024)
Law No. 32/2009 is indeed better and more perfect when compared to the previous law, so it can be said that Law No. 32/2009 is perfect in terms of legal material regulating the environment. However, can law enforcement of this law be implemented properly, because so far there have been no government regulations or other implementing regulations, so that it will cause indecisiveness against perpetrators of environmental pollution and destruction. This is where the problem lies with the existence of Law No. 32/2009 in terms of its enforcement, so that it is a warning for law enforcement officials to carry out their obligations towards perpetrators of environmental pollution and destruction in accordance with the rules that have been clearly regulated in Law No. 32/2009. The type of legal research that the author uses in compiling this legal writing is the normative juridical research type. Environmental law enforcement can also be done through civil law. This path is not popular in Indonesia because of the protracted process in court. Almost all civil cases are attempted to the highest court for cassation because the losing parties are always dissatisfied. In fact, there is a tendency for people to deliberately delay time by always using legal efforts, even though it is unreasonable, it is usually continued with a judicial review. After the decision is made, it is still often difficult to implement. Indonesian society is in reality more familiar with its natural environment than the application of technology. The development of technology that manages natural resources must provide the greatest possible benefits for the welfare of the people, while still paying attention to its balance and sustainability so that it remains beneficial for future generations. By paying attention to the quality of nature, social, culture, and economy as a commodity of the local community that is subsystem. Only human actions make it seem as if they are able to control nature so that almost all living environments have been touched by human life. Environmental law enforcement can be carried out by imposing sanctions in the form of administrative sanctions.